Unidad piloto de formación y tecnología agrícola- nodo de eco-formación logística de Tunja (2019)
For Tunja we propose the development of an urban renovation plan, which is considered as a node of logistic eco-training that manages and consolidates the territory from the different systems, improving and perfecting the different dynamics, satisfying the shortcomings and taking advantage of the potential for competitive and economic growth, with an eco-sustainable approach. Due to this, we are located in the urban area of Tunja, in a sector that has the best characteristics for the development of the plan. The proposal consists of the planning of three urban nodes, which work to rehabilitate, improve and exploit the dynamics and related activities, opting for an urban network structure, composed of natural elements, nodes of human activity and architectural equipment of regional impact.